2002
DOI: 10.1097/00004424-200206000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography-Fluoroscopy Guided Drainage of Pericardial Effusions

Abstract: Visual surveillance by CT-fluoroscopy is a feasible method in the drainage of pericardial effusions even in cases not accessible by ultrasound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…In this study patients presented with a PE (assessed by echocardiography) which was considered not drainable by ultrasound guidance. 10 It should be acknowledged, however, that different definitions (namely technical versus clinical) were used in different studies. For example, in the study by Klein and colleagues, technical success was reported in 98.4% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study patients presented with a PE (assessed by echocardiography) which was considered not drainable by ultrasound guidance. 10 It should be acknowledged, however, that different definitions (namely technical versus clinical) were used in different studies. For example, in the study by Klein and colleagues, technical success was reported in 98.4% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…2,7,8 Given these possible shortcomings in terms of image acquisition as well as the necessity for a precise needle orientation (especially in nontypical approaches), computed tomography (CT)-guided pericardiocentesis has gained interest. 6,9,10 This technique, some of the first descriptions of which concerning PE diagnosis and possible pericardiocentesis guidance were made over 30 years ago, 11,12 has been thoroughly detailed elsewhere. 6,7,13 It potentially allows overcoming many of the hindrances concerning echocardiography, and can also be relevant for the exclusion of other thoracic pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…Computed tomography-guided drainage of pericardial effusions was successfully performed in 96% of our cases (n=28), and CT-guided drainage has been proven to be reliable even when pigtail catheters are used for diagnostic purposes. Furthermore, Bruning et al [11] described the use of CT-fluoroscopy and pericardial drainage. These catheters are rigid and breakable; therefore, we preferred using the nephrostomy catheter since it is soft and unbreakable.…”
Section: Discussionmentioning
confidence: 99%
“…CT-guided pericardiocentesis is a safe and effective treatment option for patients with PE. Neves et al reported that CT-guided pericardiocentesis was successful in 94% of patients, and that unsuccessful cases had localized or organized PE, which was shown to be unsuitable for percutaneous drainage 4,8 . Furthermore, Bruning et al reported that CT-guided pericardiocentesis was successfully performed in 10 of 11 cases, including eight patients where TTE guidance was determined to be inappropriate 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Conventional echocardiography-guided pericardiocentesis is contraindicated in patients due to the absence of an optimal acoustic window, which is typically associated with chronic obstructive pulmonary disease, obesity, or post-thoracic surgery. One potential reason for the lack of guidance concerning CT-guided pericardiocentesis is that evidence supporting the competitive advantage of CT guidance over transthoracic echocardiography (TTE) is still lacking [3][4][5] . Thus, the optimal application of CT guidance for pericardiocentesis is unclear.…”
Section: Introductionmentioning
confidence: 99%